Examining The Determinants of AI Misuse Among Students in Indonesia: An Analysis Through The Fraud Diamond Framework - Andrey Hasiholan Pulungan; Rizki Ramadhan; Faris Windiarti; Meiliyah Ariani; Ahmad Basid Hasibuan (Universitas Swadaya Gunung Jati, 2025)
The growing integration of artificial intelligence (AI) in academia raises ethical concerns, particularly among business and accounting students expected to uphold professional integrity. This study examines factors influencing the use of AI for academic misconduct among Indonesian business students, applying the Fraud Diamond Theory as a framework. An online survey conducted from August 2024 to January 2025 yielded 424 valid responses, analyzed using SmartPLS version 4.1.0.9. The findings reveal that students do not view opportunity as a significant determinant of AI-assisted misconduct. Instead, capability, rationalization, and motivation significantly affect students’ intentions to engage in such behavior. This study contributes to literature and practice by highlighting ethical challenges in AI adoption within education, especially in Indonesia. It emphasizes the need for ethical AI training, enhanced digital literacy, and clear institutional protocols to address ethical dilemmas. Understanding the key drivers of AI-assisted misconduct supports the development of effective prevention and detection strategies. Given its focus on Indonesian business and accounting students, the study calls for broader validation with diverse samples and objective measures. Future research should explore the long-term impact of AI use on professional ethics, educational integrity, and intervention effectiveness.